Pseudotumor inflamatório do pulmão - Ruiz Júnior, Raul Lopes [UNESP]; Cataneo, Antonio José Maria [UNESP] (Colégio Brasileiro de Cirurgiões, 2002)
We report a case of a ten year old boy with an inflammatory pseudotumor in the right upper lobe. Surgical excision was undertaken. Inflammatory pseudotumors of the lung often occur in children. We recommend complete resection for diagnosis and cure. This tumor can mimic malignant neoplastic lesions and can recur after surgical treatment.
Inflammatory pseudotumor of the lung
Keywords: Inflammatory pseudotumor; Lung; Recurrence; Malignancy